Предмет: Математика,
автор: sergeikikot62
помооооооооогииите паааже
Приложения:
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
1) (-5/8)*(-4/5)*(-3/4)*(-2/3)*-(1/2)= - (5*4*3*2*1)/(8*5*4*3*2) = -120/960 = -1/8
2) (-7/12)*(-6/7)*(-5/6)*(-4/5)+2/3 = (7*6*5*4)/(12*7*6*5) +2/3 = 840/2520 + 2/3 = 1/3 + 2/3 = 1
3) (-11/15)*(-10/11)*(-9/10)+(-7/9)*(-6/7)+4/15 = -(11*10*9)/(15*11*10)+(7*6/9*7) + 4/15 = -9/15 + 2/3 + 4/15 = -9+10+4/15 = 5/15 = 1/3
Автор ответа:
1
Ответ: в виде фото ,надеюсь почерк понятен
Пошаговое объяснение:
Приложения:
Похожие вопросы
Предмет: Математика,
автор: pushkintown511
Предмет: Алгебра,
автор: nikyly2276
Предмет: Математика,
автор: inho4575
Предмет: Физика,
автор: Aleks10031979
Предмет: Алгебра,
автор: yanamedvedeva20